An ulcerated gastric diverticulum–a rare cause of haematemesis and melaena. Issue 708 (October 1984) - Gibbons, C. P.; Harvey, L.
Abstract : A case of recurrent intraluminal bleeding from an ulcerated gastric diverticulum is described. Difficulties in diagnosis and treatment of this rare condition are discussed. The importance of accurate preoperative diagnosis by endoscopy and barium meal is emphasized.